Endodontic treatment of severely curved root canals – A case series - Rosselle, Veronica Regina; Ongkowijoyo, Cendranata Wibawa; Setyabudi (Dental Journal (Majalah Kedokteran Gigi), 2024)
Background: It is not uncommon for a dentist to encounter endodontic cases of severely curved root canals. Performing endodontic treatment on severely curved root canals can be a daunting task due to the notable risk of creating an iatrogenic error including ledge, perforation, or even instrument separation. Therefore, radiograph image analysis, proper endodontic treatment planning, selection of appropriate instruments and technique is essential to ensure success in endodontic treatment of severely curved root canals. Purpose: This case series aims to elaborate the instruments and technique to safely negotiate, clean, shape, and seal root canals with severe curvature. Cases: Three patients came to Universitas Airlangga Dental Hospital due to a severe toothache. After anamnesis and examination, diagnosis was established, and endodontic treatment was deemed necessary. During radiographic image analysis, it is visible that the root canal had a severe curvature. Case Managements: Access opening was performed to allow a straight-line access, orifices were preflared, root canals were negotiated, and glide path was established. Then, shaping, cleaning, and sealing can be performed conveniently until the root canal terminus. Subsequently, coronal restoration was fabricated to restore function and esthetics. Conclusion: With proper knowledge, case analysis, appropriate instruments and techniques, severely curved root canals can be safely and predictably negotiated, cleaned, shaped, and sealed.